Diskursus Walāyah dalam Pemikiran Mistik Ruzbihan Baqli dan Haydar Amuli - Fuad, Ahmad Nur (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2016)
This article seeks to explore the mystical thoughts of two influential sufis, Ruzbihan Baqli and Haydar Amuli, on sainthood (walāyah). It argues that both sufis represent a typical flavor of Sufism, in that the former placed emphasis on Persianate cultural vocabularies, while the latter was characterized by the integration of Sufism and Shiism and the incorporation of the philosophical or metaphysical views of Ibn ‘Arabī into Imāmī Shī‘ī mysticism. Although Baqli was not the first to develop the concept of walāyah, his exposition of the issue exhibits a typically Persianate symbolism of sufism. His mystical experiences, based on his spiritual visions, confirm that the wali like him occupies a special status next to the prophets, and in particular the Prophet Muhammad. Amuli asserted that the seal of universal walāyah is ‘Alī b. Abī Ṭālib, and that the twelfth imam or the Mahdi was the seal of Muhammadan walāyah. This view is different from Ibn ‘Arabī’s that the seal of universal walāyah is Jesus. Both mystics’ views on walāyah can be traced back to their predecessors and their legacies can be revealed from the following sufis after both respectively.